IMPLEMENTASI HASIL PELATIHAN BAGI PENDIDIK ( PAUD) TINGKAT PEMULA DALAM PROSES PEMBELAJARAN ANAK USIA DINI - Nursam Nursam (Universitas Insan Cendekia Mandiri, 2019)
The theoretical basis of this research is bihaviorisme learning theory, behaviorism learning theory is a theory about a change in behavior as a result of experience. This theory is considered as the basis for a wide range of innovative programs in education both formal and non-formal education. This study used a qualitative approach. Subjects were early childhood tutor / educators, and parents. as the primary data source. The purpose of learning is the formation of behavior and development aspects of the basic skills of early childhood. Tutor using various methods and approaches to learning; evaluation carried out during the learning process with the techniques of observation and portfolios; the development aspects of the basic skills of children includes cognitive and affective aspects psikimotor. Learning methods are often used by tutors is the method of storytelling and role playing. Activity game that stands out is the game outdoors. Learners experience changes in cognitive, apektif, psychomotor, after participating in learning activities in group play. Learners have improved aspects of basic capabilities, of thirty-headed (37) children less than eighty percent (80%) of the children could read.